2018
DOI: 10.1007/s00217-018-3118-0
|View full text |Cite
|
Sign up to set email alerts
|

Foaming characteristics of oat protein and modification by partial hydrolysis

Abstract: Foaming ability of oat protein isolate (OPI) was analysed at pH 4 and 7. Foaming properties were influenced by partial hydrolysis with trypsin (OPT) and alcalase (OPA). The viscoelasticity of the protein film, the interactions between the protein molecules, and the network forming within the protein film were analysed by interfacial rheology. At pH 7, foams made of OPI and OPT were found to be stable with OPI having the fastest foaming ability. At pH 4, the foaming properties of OPI were found to be poor due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…However, Autio et al [62] using trypsin observed that viscosity of β-glucan samples was lowered, which could confirm existing interactions between protein and polysaccharides like β-glucan. The more pronounced action from the papain also may be allocated both to the residual β-glucanasic activity or strong cleavage action towards protein-β-glucan linkages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Autio et al [62] using trypsin observed that viscosity of β-glucan samples was lowered, which could confirm existing interactions between protein and polysaccharides like β-glucan. The more pronounced action from the papain also may be allocated both to the residual β-glucanasic activity or strong cleavage action towards protein-β-glucan linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Oat globulins showed a limited solubility under acidic conditions. Researchers [62,64] observed the protein particles with hexameric structures at pH 7 whereas at pH 4 the protein structures were smaller than 20 kDa. In other works, the solubility of oat proteins has increased in highly acidic conditions (pH 1–4) [38,40,48,50] but, the present study did not consider pH beneath 3.…”
Section: Discussionmentioning
confidence: 99%
“…A commercial mixture of peptides, ranging from 10 to 170 kDa, was used as marker (cat# 26616, Thermo Scientific). SEC was carried out on HPLC ÄKTAbasic TM 10 (Amersham Biosciences, Sweden), according to Brückner-Gühmann et al (2018). The analysis was performed using phosphate buffer at pH 7.…”
Section: Chickpea Protein Extraction and Characterizationmentioning
confidence: 99%
“…Furthermore, Brückner‐Gühmann et al. (2018) evaluated the foamability of OPI hydrolyzed with trypsin, and showed that stable and fast forming foams can be prepared from hydrolyzed OPI at pH 4 and 7. Brückner‐Gühmann et al.…”
Section: Techno‐functional Properties Of Oat Proteins and Their Application In Food Industrymentioning
confidence: 99%